Bioimaging: In Vivo Photoacoustic Imaging of Livers Using Biodegradable Hyaluronic Acid‐Conjugated Silica Nanoparticles (Adv. Funct. Mater. 22/2018). (28th May 2018) - Lee, Donghyun; Beack, Songeun; Yoo, Jounghyun; Kim, Su‐Kyoung; Lee, Changho; Kwon, Woosung; Hahn, Sei Kwang; Kim, Chulhong
Abstract : In article number1800941, Woosung Kwon, Sei Kwang Hahn, Chulhong Kim, and co‐workers describe hyaluronate–silica‐nanoparticle (HA–SiNP) conjugates for liver‐specific delivery and imaging. The HA–SiNP conjugates show high liver‐specific targeting efficiency, strong optical absorbance in near‐infrared windows, excellent biocompatibility, and biodegradability. The liver‐specific targeting efficiency is verified by in vitro cellular uptake tests, and in vivo and ex vivo photoacoustic imaging.